Postponement for Designing Mass-Customized Supply Chains: Categorization and Framework for Strategic Decision Making - Seung-Hwan Kim (International Journal of Supply Chain Management, 2014)
The concept of mass-customization has been suggested as the mandatory capability in the 21st century market place where customers individual need must be satisfied rather than the need of mass market. Postponement is a powerful methodology to achieve Cost-effective mass customization when applied in the scope of supply chain. There have been a number of literatures that employed postponement or reviewed postponement in a complex manner but not much on providing a simple framework practitioners can easily apply for establishing the level of implementing postponement to their supply chains. In this paper the classificationof the postponement in terms of level of implementation and the strategic decision framework for selecting the right postponement that considers realistic aspect of recent economy are presented.